Determination of plasma velocity from light fluctuations in a cutting torch - Prevosto, L. (2009)
Measurements of plasma velocities in a 30 A high energy density cutting torch are reported. The velocity diagnostic is based on the analysis of the light fluctuations emitted by the arc which are assumed to propagate with the flow velocity. These light fluctuations originate from plasma temperature and plasma density fluctuations mainly due to hydrodynamic instabilities. Fast photodiodes are employed as the light sensors. The arc core velocity was obtained from spectrally filtered light fluctuations measurements using a band-pass filter to detect light emission fluctuations emitted only from the arc axis. Maximum plasma jet velocities of 5000 m s -1 close to the nozzle exit and about 2000 m s -1 close to the anode were found. The obtained velocity values are in good agreement with those values predicted by a numerical code for a similar torch to that employed in this work. © 2009 American Institute of Physics.